Improving the electrochemical performances using a V-doped Ni-rich NCM cathode - Sim, Seoung-Ju (Sci Rep, 2019)
Ni-rich layered LiNi(0.84)Co(0.10)Mn(0.06)O(2) cathode material was modified by doping with vanadium to enhance the electrochemical performances. The XRD, FESEM and XPS analyses were indicated that the vanadium is successfully doped in the crystal lattice of LiNi(0.84)Co(0.10)Mn(0.06)O(2) with high crystallinity. 0.05 mol% vanadium doped LiNi(0.84)Co(0.10)Mn(0.06)O(2) exhibits superior initial discharge capacity of 204.4 mAh g(−1), cycling retention of 88.1% after 80 cycles and rate capability of 86.2% at 2 C compared to those of pristine sample. It can be inferred that the vanadium doping can stabilize the crystal structure and improve the lithium-ion kinetics of the layered cathode materials.